2011
DOI: 10.4067/s0034-98872011000800005
|View full text |Cite
|
Sign up to set email alerts
|

Factores vinculados a la calidad de vida en la adultez mayor

Abstract: Quality of life of older people living in Antofagasta, Chile Background: As basic needs of older people are covered, the concern about the determinants of their quality of life becomes preeminent. Aim: To evaluate the relationship between self-reported quality of life and related variables. Material and Methods: The Quality of Life Survey for older people developed by the World Health Organization (WHOQOL-Old), the reduced scale of Ryff Psychological Well Being, the Functional Social Support Questionnaire, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
2
26

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 24 publications
1
7
2
26
Order By: Relevance
“…Similar findings were reported in a study by Urzúa et al, 24 in which individuals who were not sick significantly valued social support and their purpose in life. The same situation was also described by Osorio et al 25 and by Rivas et al 19 , who concluded that "social relations and support networks represent the heart of the social interaction of the elderly".…”
Section: Discussionsupporting
confidence: 79%
“…Similar findings were reported in a study by Urzúa et al, 24 in which individuals who were not sick significantly valued social support and their purpose in life. The same situation was also described by Osorio et al 25 and by Rivas et al 19 , who concluded that "social relations and support networks represent the heart of the social interaction of the elderly".…”
Section: Discussionsupporting
confidence: 79%
“…A study done in older people in Antofagasta, Chile, found that people perceiving themselves as sick had significantly lower quality of life (Urzua et al 2011). On the other hand, Fuentes-García et al (2012) studied the oral health-related QoL in Santiago and two other Latin American cities showing a strong association with educational level.…”
Section: Introductionmentioning
confidence: 99%
“…En esta línea, los adultos mayores experimentan diversas dolencias o enfermedades, pero destaca la "capacidad de adaptación" a sus nuevas condiciones o bien limitaciones para hacer frente a los problemas propios de la cotidianeidad. Finalmente, el pertenecer a un entorno físico protegido, ya sea la vivienda o el barrio, que se perciba como un espacio alejado de problemas sociales de violencia, drogadicción o alcoholismo (Herrera, Barros y Fernández, 2011;Osorio, Torrejón y Anigstein, 2011;Torres et al, 2008;Urzúa, et al 2011).…”
Section: Calidad De Vida Y Género En La Vejezunclassified
“…No obstante, en un análisis más específico en las posibles diferencias de género y calidad de vida, se obtienen los siguientes hallazgos: ser mujer se asocia con una peor percepción de bienestar, así como una menor capacidad funcional y un menor ingreso (Herrera, Barros y Fernández, 2011) y las mujeres tienen una mayor participación social (Urzúa, et al 2011). Pero estos estudios no se centran en analizar de manera específica las posibles diferencias de género, más bien analizan las diferencias por sexo, en la calidad de vida de las personas mayores chilenas y las condiciones de salud (independencia en AVD y problemas de salud).…”
Section: Calidad De Vida Y Género En La Vejezunclassified